2023
DOI: 10.3390/app13084782
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Body Composition between Playing Positions in Men’s Professional Soccer: A Systematic Review with Meta-Analysis

Abstract: The performance of male soccer players (MSPs) depends on multiple factors, such as body composition. It is understandable to think that, due to the physical demands and specific functions during play, body composition may vary depending on the playing position. The aim of this systematic review and meta-analysis was to describe the anthropometric, BC, and somatotype characteristics of professional MSPs and to compare the reported values according to playing position. We systematically searched Embase, PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…Research suggests that during a match, the midfielder and forward positions are the most physically active playing positions [76][77][78]. Furthermore, research has shown that these positions are associated with lower levels of body fat [79], indicating a higher energy expenditure. Our study found a positive association between these positions and a higher caffeine intake.…”
Section: Influence Of Competitive Level Playing Position and Sexmentioning
confidence: 99%
“…Research suggests that during a match, the midfielder and forward positions are the most physically active playing positions [76][77][78]. Furthermore, research has shown that these positions are associated with lower levels of body fat [79], indicating a higher energy expenditure. Our study found a positive association between these positions and a higher caffeine intake.…”
Section: Influence Of Competitive Level Playing Position and Sexmentioning
confidence: 99%
“…Nutrient intake can have a profound impact on a player's body composition and performance favoring a similarity with elite soccer patterns, where scientific literature advocates that each playing position shows specific characteristics due to different physical demands and roles during training and, especially, in competitions [3,6,7,64]. Therefore, it is recommended to take care of the nutrition of all players and, if possible, to individualize the nutrition based on the playing position.…”
Section: Influence Of Playing Position On Nutritionmentioning
confidence: 99%
“…There are two main categories: the base and the professional one, with the base category (U19-10) being the one played Nutrients 2023, 15, 4323 2 of 14 by young people before reaching the professional leagues (1st and 2nd in Spain) [4]. It is well known that body composition [5][6][7], as well as hydration, healthy eating habits and supplementation [3,8,9], are associated with physical performance among elite athletes. Understanding how these factors, along with playing position, may influence the nutritional intake of soccer players is essential for the design of nutrition education programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, different playing positions have varying anthropometric characteristics and physical demands during matches. Therefore, hydration needs may differ between matches and training [ 23 , 24 , 25 , 26 ]. Finally, it is important to consider that total daily fluid requirements may vary with age.…”
Section: Introductionmentioning
confidence: 99%